Enhancing phosphorus use efficiency and soil quality indicators in lowland paddy ecosystem through Azolla, rice straw, and NPKS fertilizers - Marzouk, Said H.; Tindwa, Hamis J.; Amuri, Nyambilila A.; Chande, Hashim H.; Semoka, Johnson M. (Frontiers in Agronomy, 2024)
Purpose: This study investigates the influence of incorporating Azolla, rice straw, and NPKS fertilizers on phosphorus use efficiency (PUE) and rice productivity in lowland paddy fields. Despite Azolla's well-known role as a nitrogen-fixing aquatic fern in rice production, its specific impact on PUE remains unclear. The primary objective is to explore diverse treatment combinations to identify synergies that enhance both PUE and overall rice productivity.The study Conducted at Mkula irrigation scheme in the Kilombero Valley, Tanzania, the field experiment employed a Randomized Complete Block Design with thirteen treatments and three replications. Treatments comprised various combinations of Azolla, rice straw, and chemical fertilizers, incorporating 50 and 100% rates of nitrogen (N) applied with phosphorus (P), potassium (K), and sulfur (S).Results: The study reveals the substantial impact of Azolla application on total nitrogen, available phosphorus, and exchangeable potassium levels in the soil. Particularly noteworthy were treatment combinations involving Azolla, rice straw, and reduced rates of synthetic nitrogen, along with specific P, K, and S applications, which exhibited the highest phosphorus uptake and PUE. Specifically, combining rice straw and Azolla with reduced N rates, alongside 30 kg P ha-1 + 30 kg K ha-1 + 20 kg S ha-1, resulted in the highest phosphorous uptake (73.57 kg/ha) and PUE (46.24%).Conclusions: Integrated nutrient management, incorporating rice straw and Azolla alongside synthetic fertilizers, demonstrates synergistic effects on phosphorus uptake and efficiency while maintaining soil quality. The study underscores the potential of such integrated strategies to optimize PUE and contribute to sustainable rice production in lowland paddy fields.